The Influence of Teacher Competence and the use of Interactive Wordwall Media on Early Literacy Abilities of Early Childhood - Supriyadi, Supriyadi; fahria, Siti Utami Agustina; Zulfah, Fahria (International Journal of Business, Law, and Education, 2025)
This study aims to reveal the Influence of Teacher Competence and the Use of Interactive Wordwall Media on Early Childhood Literacy Skills. This study is a quantitative study with a survey approach. The population in this study were Kindergarten students at the Selaras Auladia Foundation, North Cikarang. This study used a saturated sample of 50 early childhood children. The research data was obtained through valid and reliable instruments. This study aims to analyze the Influence of Teacher Competence and the Use of Interactive Wordwall Media on Early Childhood Literacy Skills. The trial of the Teacher Competence instrument obtained a reliability of  0,784 and the interactive wordwall media instrument obtained a reliability of 0,788. The results of the analysis show that teacher competence has a positive effect on early childhood literacy skills, and the use of interactive wordwall media has a positive effect on early childhood literacy skills. Teacher competence and the use of interactive wordwall media together have an effect on early childhood literacy skills.